Isolation and Characterization of Hemicellulose from Empty Oil Palm Fruit Bunches - Miswanda, Dikki; Savika, Anggraini; Syafirna, Nada; Sitompul, Maysaro; Selly, r; Zubir, Moondra (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
Isolation and characterization of hemicellulose from empty oil palm bunches have been carried out. The method used in the isolation is alkali extraction with NaOH solvent. Hemicellulose isolated from empty oil palm bunches was analyzed by organoleptic and solubility tests. Functional group analysis was carried out using FTIR, and morphology was performed using SEM. The highest yield of 12.84% was obtained from the variation of 0.5 N NaOH solvent. Organoleptic and solubility tests showed that the characteristics of hemicellulose isolated from empty oil palm bunches were by the characteristics of hemicellulose in general. The FTIR results of hemicellulose showed the specific absorption peaks of OH stretching, C-H stretching, C=O bending, C-OH bending, and C-C stretching. SEM photos show the rough and fibrous shape of the hemicellulose powder surface.